Addressing medical absenteeism in pre-vocational secondary students: effectiveness of a public health intervention, using a quasi-experimental design - Yvonne T. M. Vanneste; Jolanda J. P. Mathijssen; Ien A. M. van de Goor; Carin M. C. Rots - de Vries; Frans J. M. Feron (BMC, 2016)
Abstract Background Students' health and school absenteeism affect educational level, with adverse effects on their future health. This interdependence is reflected in medical absenteeism. In the Netherlands, a public health intervention has been developed to address medical absenteeism in pre-vocational secondary education. This study aims to investigate the effectiveness of this intervention on students' medical absenteeism, compared to "medical absenteeism policy as usual". Methods A quasi-experimental design with an intervention group (493 students) and a control group (445 students) was applied. Multilevel analysis was used to study differences in the development of the level of a student's medical absence over time (after 3 and 12 months). Results In the intervention group, the level of absenteeism decreased from 8.5 days reported sick in 12 school weeks to 5.7 days after 3 months, and to 4.9 days after 12 months. The number of absence periods fell from 3.9 in 12 school weeks to 2.5 after 3 months, and to 2.2 after 12 months. In the control group, the absence days initially decreased from 9.9 days reported sick in 12 school weeks to 8.4 days after 3 months, after which an increase to 8.9 days was measured. The number of absence periods initially decreased from 4.5 in 12 school weeks to 3.5, after which an increase to 3.7 was measured. The number of absence days per period remained about the same in both groups. Conclusions The study provides first indications for the intervention to be effective for Dutch pre-vocational secondary students with increased medical absence rates. The intervention, which consists of personalised management of medical absenteeism by systematic identification of students with extensive medical absenteeism and consistent referral to youth health care physicians, appears to reduce the absence rates more effectively than "medical absenteeism policy as usual". The effectiveness of the intervention is shown primarily by a decrease in the number of periods reported sick.